Upaya Meningkatkan Kebugaran Fisik Siswa Dengan Penjasorkes - Raditya Pratama; Ruman Ruman; M. Aditya Panca Putra (Badan Penerbit STIEPARI Press, 2022)
This research aims to describe and examine related issues in physical education. The issue or problem raised in this article is about physical fitness in school students. The 2022 Sport Development Index (SDI) shows the condition of physical strength/physical fitness of the Indonesian people: 0.07% is in the superior category; 1.6% excellent; 3.5% good; 9.7% moderate; 23.9% less; and 60.1% very little. Based on the low level of physical fitness of students in Indonesia, there must be a solution to this problem. Through physical education given to students at school, so far it has not had an effect on increasing students' physical fitness. Therefore, improvements are needed in the management of physical education learning in schools. With good learning management, it will be possible to improve students' physical fitness, and be in line with the goals of physical education.